2004
DOI: 10.1124/mol.65.4.832
|View full text |Cite
|
Sign up to set email alerts
|

Src and Cas Are Essentially but Differentially Involved in Angiotensin II-Stimulated Migration of Vascular Smooth Muscle Cells via Extracellular Signal-Regulated Kinase 1/2 and c-Jun NH2-Terminal Kinase Activation

Abstract: Angiotensin II (Ang II) plays an important role in several cardiovascular diseases associated with vascular smooth muscle cell (VSMC) growth and migration. Src activity is known to be required for the migration of a number of cell types. p130Cas was reported to be essential for cell migration and actin filament reorganization. Mitogen-activated protein (MAP) kinases were also reported to be critical regulatory factors for growth and migration of VSMC. However, precise intracellular mechanisms involving c-Src, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 44 publications
4
72
1
1
Order By: Relevance
“…Nifedipine potently inhibited PDGF-induced Src activation and tyrosine phosphorylation of Cas, paxillin, and cortactin, all of which have been implicated in cell migration [16][17][18] . Indeed, Kyaw and colleagues reported that Cas is involved in Anginduced VSMC migration 23) , and we previously used RNA interference techniques to demonstrate that Cas, cortactin, and paxillin are required for VSMC migration (unpublished data). Thus, the present data suggest that nifedipine inhibits VSMC migration via the inhibition of Src activation.…”
Section: Discussionmentioning
confidence: 99%
“…Nifedipine potently inhibited PDGF-induced Src activation and tyrosine phosphorylation of Cas, paxillin, and cortactin, all of which have been implicated in cell migration [16][17][18] . Indeed, Kyaw and colleagues reported that Cas is involved in Anginduced VSMC migration 23) , and we previously used RNA interference techniques to demonstrate that Cas, cortactin, and paxillin are required for VSMC migration (unpublished data). Thus, the present data suggest that nifedipine inhibits VSMC migration via the inhibition of Src activation.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are believed to be associated with the migration and proliferation of vascular smooth muscle cells (15,16). Migration, proliferation, and MAPK activation can occur in vascular smooth muscle cells stimulated by Ang II (5,20,21). Growth factors and cytokines activate the p38 MAPK pathway, which mediates cell migration in tracheal smooth muscle cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of p38 MAPK leads to the contraction, migration, and proliferation of vascular smooth muscle cells (17 -19). Ang II is known to stimulate the activation of MAPKs, including extracellular signal-regulated kinase (ERK) 1 / 2, p38 MAPK, and stress-activated protein kinase / c-Jun Nterminal kinase in vascular smooth muscle cells (9,20,21). Previously, we have shown that the p38 MAPK pathway is involved in spleen tyrosine kinase (Syk)-induced migration in response to platelet-derived growth factor (PDGF) in vascular smooth muscle cells (3).…”
Section: Introductionmentioning
confidence: 99%
“…7,15 Therefore, we have investigated the possible signaling cross-talk between Rho/ROCK activation and the MAPK family activation by Ang II. As shown in Figure 2A, Ang II-induced ERK and p38MAPK phosphorylations were not affected by dnRho.…”
Section: Activation Of Rho/rock Is Required For Ang Ii-stimulated Migmentioning
confidence: 99%